2019
DOI: 10.4236/as.2019.107069
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of <i>Miscanthus</i> Cultivation on the Biodiversity of Ground Beetles (Coleoptera: Carabidae), Spiders and Harvestmen (Arachnida: Araneae and Opiliones)

Abstract: In-crop invertebrate biodiversity of the perennial rhizomatous biomass cropMiscanthus was compared to the in-crop invertebrate biodiversity of adjacent agricultural land-uses. Ground beetles and arachnids (spiders and harvestmen) were used as indicators of invertebrate biodiversity and caught using pitfall traps over two years. Biodiversity measurements used were species richness, biomass, abundance, Simpson's Index, and rarity values. The Miscanthus plantation had a significantly lower ground beetle and arach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…However, the underlying implications for this are less obvious, and caution is required when making general assumptions. For instance, it has been shown that the impacts of the plantation of perennial crops may range from positive to even negative impacts on biodiversity compared to annual crops [97,[103][104][105][106][107]. For example, miscanthus cultivation supports earthworm communities [89], but it does not provide nectar and pollen for pollinators as do wide crop rotations including flower-rich catch crops such as flax (Linum usitatissimum L.), lucerne (Medicago sativa L.) and Phacelia (Phacelia tanacetifolia Benth.)…”
Section: Bioenergy Crop Cultivation and Biodiversitymentioning
confidence: 99%
“…However, the underlying implications for this are less obvious, and caution is required when making general assumptions. For instance, it has been shown that the impacts of the plantation of perennial crops may range from positive to even negative impacts on biodiversity compared to annual crops [97,[103][104][105][106][107]. For example, miscanthus cultivation supports earthworm communities [89], but it does not provide nectar and pollen for pollinators as do wide crop rotations including flower-rich catch crops such as flax (Linum usitatissimum L.), lucerne (Medicago sativa L.) and Phacelia (Phacelia tanacetifolia Benth.)…”
Section: Bioenergy Crop Cultivation and Biodiversitymentioning
confidence: 99%
“…The long period of soil dormancy and the low use of pesticides and synthetic fertilizers in Miscanthus cultivation offers a number of ecological advantages (Heaton et al, 2008; Von Cossel, Lewandowski, et al, 2019), for both the cultivation site (agroecosystem) (Felten & Emmerling, 2011; Jørgensen et al, 2014; Williams & Feest, 2019) and adjacent ecosystems such as flowing or stagnant water bodies (Christian & Riche, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, biomass crops should be grown on marginal agricultural land, where food production is compromised by adverse climatic, geographical, geological, or economic factors (Carlsson et al, 2017; Fernando et al, 2015, 2018; Galatsidas et al, 2018; Gelfand et al, 2013; Gopalakrishnan et al, 2011; Lask et al, 2019; Nabel et al, 2018; Von Cossel, Lewandowski, et al, 2019; Wagner et al, 2019; Xue et al, 2016). Perennial biomass crops have distinct advantages on above‐ and below‐ground biodiversity (Bellamy et al, 2009; Williams & Feest, 2019), soil fertility, groundwater protection (Ferrarini et al, 2017; Mishra et al, 2019), climate change mitigation (Clifton‐Brown et al, 2017; Emmerling & Pude, 2017; McCalmont et al, 2017), and carbon sequestration (Bui et al, 2018; Canadell & Schulze, 2014). Hence the production of perennial crops on marginal agricultural land carries the potential to restore degraded agricultural lands, which, at a later stage, can (again) become attractive for food production (Barbosa et al, 2015, 2018; Fiorentino et al, 2018; Pogrzeba et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the literature mostly discussed the environmental and economic benefits of energy crops growing, but now scientists identify a number of associated risks: the impact on land and water resources, biodiversity, changes in agriculture [Pidlisnyuk and Kolisnyk, 2013; Renewable energy in Europe..., 2019; Williams and Feest, 2019]. Allelopathy is one of the potential important risks associated with the growth of energy crops.…”
Section: Introductionmentioning
confidence: 99%